2015
DOI: 10.2135/cropsci2014.03.0199
|View full text |Cite
|
Sign up to set email alerts
|

Crop Rotation and Management Effect on Fusarium spp. Populations

Abstract: Fusarium spp. are common fungal pathogens that infect a number of field and vegetable crops. Crop rotation, genetic resistance, and fungicides are the primary methods used for managing these pathogens; however, there is a lack of information regarding the interactions between these management strategies and how they impact Fusarium spp. population dynamics. Therefore, the objective of this research was to quantify the effect of crop rotation and management (i.e., variety selection and fungicide use) on F. gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 59 publications
2
35
1
Order By: Relevance
“…However, in their study they observed that the F. virguliforme population was not quantifiable from fields with wheat in rotation. Results of our microplot studies with diverse crop residue amendment are in agreement with findings of Almeida et al [29], Cotten and Munkvold [30] and Kommedahl et al [31] but differ from Marburger et al [32] for F. virguliforme.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in their study they observed that the F. virguliforme population was not quantifiable from fields with wheat in rotation. Results of our microplot studies with diverse crop residue amendment are in agreement with findings of Almeida et al [29], Cotten and Munkvold [30] and Kommedahl et al [31] but differ from Marburger et al [32] for F. virguliforme.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Marburger et al [32] observed no significant effect of crop rotation sequences and management (variety selection and fungicide use) on F. oxysporum and F. virguliforme. However, in their study they observed that the F. virguliforme population was not quantifiable from fields with wheat in rotation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of controlling Fusarium spp. causing FCR is also accentuated by Marburger et al (2015) who noted that none of the management strategies employed in their study significantly reduced F. oxysporum. …”
Section: Discussionmentioning
confidence: 87%
“…However, the parallel study examining the influence of these management practices on Fusarium spp. populations found F. virguliforme was present in 6.2% of plots examined (Marburger et al, 2015). Because F. virguliforme was present but SDS symptoms were not observed, this may only partially explain why the RRR rotation yielded the highest.…”
Section: Resultsmentioning
confidence: 99%
“…To examine interactions among multiple disease management practices, a comprehensive study was designed and implemented to meet two objectives: (i) identify possible combinations of practices that could reduce risk of disease development by decreasing Fusarium spp. populations (Marburger et al, 2015); and (ii) quantify the effect of combinations of these practices on yield (current study). In an earlier study, Marburger et al (2015) showed that there were few interactions among crop rotation, cultivar selection, and fungicide use that reduced soil populations of three Fusarium species, with significant interactions or individual control methods dependent on the species being examined.…”
mentioning
confidence: 99%